The choice of address terms between the intention of the speaker, the interpretation of thereceiver and social requirements: analysis of verbal interactions in the Gharb region inMorocco. (مجلة إحالات, 2026)
This article represents the outcome of an intense research that has been going on since 2018. It is considered as a product of our project through highlighting the obtained results and their analysis. It sheds light on courtesy and verbal violence; these two subjects are controversial, they always exist in our society through various communicational situations.It pushes the speaker to choose either an appropriate or inappropriate term of address depending on thewillingness and the intention of the speaker or the interpretation of the receiver. It was very crucialfrom us to write this article in order to show the procedures taken through the preparation of thisproject.